The Meaning of the Word Patience in the Study of Tafsir Maudhu'i - Alhakimi, Imam Mujaddid; Imawan, Dzulkifli Hadi (Pascasarjana IAIN Metro, 2023)
Abstract One of the purposes behind the revelation of the Qur'an is to serve as a guiding light for humanity. However, the content of the Qur'an, including its verses and passages, often possesses a universal nature, necessitating specialized expertise in interpreting it through various methodologies, among which is the maudhu'i interpretation. The term